(untitled) (Philological Studies, 2019)
The article «Steven Heym’s Historical Novels «King David Report» and «Ahasver»: Demythologized History and Historical Reflection» touches upon the German historical prose of 1970–80-ies. Its poetical peculiarities are revealed on the example of S. Heym’s «King David Report» (1972) and «Ahasver» (1981). Distrust to the traditional view of history and criticism of the Enlightenment ideology compel the authors of historical stories (S. Heym, G. Grass, Ch. Wolf) to appeal to the sources of European history. S. Heym uses the critical potential of a myth: as foundation for his novels the author takes the Bible legends about King David and fallen angels. In Heym’s works the author’s attention is focused on reflecting person upon the historical background that allows a reader to penetrate into the great history through the prism of a private experience. The main narrative message of Heym’s novels is expressed through the historical responsibility problem that is particularly burning in the light of the present-day situation of changing values.